PENGARUH FAKTOR-FAKTOR EKONOMI GREENHOUSE GAS EMISSION DISCLOSURE DAN PENGARUHNYA TERHADAP REAKSI SAHAM - Ratu Persada Pahlevi Pasca Mahardika; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to investigate the effect of leverage, financial slack, company’s growth, and profitability on greenhouse gas disclosure and stock reaction. The sample is based on 27 manufacturing companies listed on The Indonesia Stock Exchange during period 2013-2017. This research uses multiple regression analysis to test the research hypothesis. The result of this study show that leverage affect positive significantly on greenhouse gas disclosure, and leverage, company’s growth, and  profitability affect positive significantly on stock reaction.